2020
DOI: 10.1186/s12889-020-8433-2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards viral haemorrhagic fevers amongst healthcare workers in urban and rural public healthcare facilities in the N’zérékoré prefecture, Guinea: a cross-sectional study

Abstract: Background: The 2013-2016 Ebola epidemic in West Africa began in Guinea's Forest region, a region now considered to be at high risk for future epidemics of viral haemorrhagic fevers (VHF). Good knowledge, attitudes and practices towards VHF amongst healthcare workers in such regions are a central pillar of infection prevention and control (IPC). To inform future training in IPC, this study assesses the knowledge, attitudes and practices (KAP) towards VHF amongst healthcare workers in public healthcare faciliti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 21 publications
7
26
1
Order By: Relevance
“…Our study shows that HCWs in Makerere University Teaching Hospitals have good COVID-19 prevention practices similar to findings by Alfahan et al on coronaviruses (29), Raab et al on Ebola Virus Disease in Guinea (30) and in the general population of the Chinese on COVID-19 (19). Majority of the HCWs are following infection prevention and control practices recommended by the Ministry of Health Uganda and WHO.…”
Section: Discussionsupporting
confidence: 87%
“…Our study shows that HCWs in Makerere University Teaching Hospitals have good COVID-19 prevention practices similar to findings by Alfahan et al on coronaviruses (29), Raab et al on Ebola Virus Disease in Guinea (30) and in the general population of the Chinese on COVID-19 (19). Majority of the HCWs are following infection prevention and control practices recommended by the Ministry of Health Uganda and WHO.…”
Section: Discussionsupporting
confidence: 87%
“…The inappropriate adherence of hand hygiene may induce terrible cross-infection between HCWs and patients, causing unnecessary morbidity, mortality and healthcare cost [3]. Current studies have explored the impact of knowledge, attitude, awareness and sociodemographic characteristic on hand hygiene comprehensively, while the impact of psychological status is little known [4][5][6][7]. Although Colindres and Manomenidis found that burnout was the predictor of lower hand hygiene, the small sample size limited the generalization of the two studies [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements are needed for employers as well as managers and administrators to enhance the availability of guidelines; moreover, there should be instructions or templates to develop guidelines and measures provided by health authorities as a reference for employers to follow and develop their own version. Adequate training for infection control can be made available to employees to improve their awareness and hygiene practice based on experiences from outbreaks and epidemics of other diseases [16,21]. Among the different occupations, more efforts are required to provide workplace prevention guidelines and measures for manual labourers, including service workers/sales/craft workers, plant/machine operators, and assemblers and elementary workers, as their reported availability of such guidelines was lower, and some of them, such as service/sales workers, are exposed to a higher risk than others because of having more frequent contact with other individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was developed based on a related study [16] and WHO guidelines for COVID-19 prevention in workplace [8]. This study focused on two major aspects as follows: 1) availability of workplace guidelines and measures for preventing COVID-19; 2) frequency in past 7 days of personal protection behaviours; eight behaviours under four categories were assessed: hand hygiene (handwashing before meals, handwashing after using the toilet, use of alcohol-based hand rub when outside), face mask (wearing face mask when outside), household hygiene (putting disinfectant into toilets, putting disinfectant into drain-pipe), social distancing (avoiding leaving home, avoiding contact with neighbours).…”
Section: Instruments and Measuresmentioning
confidence: 99%